A new generation of consumers? A study on the pro-environmental behavior of the Fridays for Future generation based on the social identity approach - Bauernschmidt, Verena; Beitz, Beatrice; Schröder, Hendrik (Frontiers in Sustainability, 2023)
Especially for the younger generation, climate change is a threat, and therefore, environmental protection and pro-environmental behaviour (PEB) are most important. The Fridays for Future movement speaks up for the young generation. Based on the social identity approach, the study is the first to investigate the role of stereotypes related to identification with the movement as a political expression of youth. Using structural equation modelling (n=543), the study demonstrates that identification is higher when pupils connect the movement with positive stereotypes, aligning with previous research findings for other activists, such as feminists. Whereby environmental concern has an additionally significant but low impact on identification, pro-material value orientation has no effect. Furthermore, the study investigates the relationship between identification with the movement and different types of PEB. The relationship is strongest with public sphere PEB in the form of future participation in a demonstration of the movement. Nevertheless, there is also a positive relationship with private sphere PEB such as nature-compatible actions in everyday life, for example, a meat-free diet and buying an environmentally friendly product. This is partly additionally confirmed through a conjoint analysis also conducted as part of the study. These findings enhance the understanding of the relationship between activism and different types of PEB among pupils and they contribute to closing this research gap. Finally, the implications and limitations of the work are discussed, along with an outlook for future research.